2022
DOI: 10.2166/wcc.2022.005
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal trend analysis and future projections of precipitation at regional scale: a case study of Haryana, India

Abstract: In this study, we investigated the spatio-temporal distribution and performance of seasonal precipitation in all districts of Haryana, India. We analysed the gridded precipitation dataset of the India Meteorological Department (IMD) for a period of 120 years (1901–2020) using different statistical methods. We found that Haryana received a mean precipitation of 37.0, 37.7, 468.3, and 24.8 mm during the winter, pre-monsoon, monsoon, and post-monsoon seasons, respectively. During each season, the eastern district… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 72 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…For India, a few literatures are available for extreme precipitation analysis 30,[42][43][44] , however relatively fewer for extreme precipitation modelling using machine learning 37,45,46 . The limited availability of highquality and comprehensive meteorological data in India and complexity of the regional topography and climate are also prominent contributing factor for limited number of research.…”
Section: Introductionmentioning
confidence: 99%
“…For India, a few literatures are available for extreme precipitation analysis 30,[42][43][44] , however relatively fewer for extreme precipitation modelling using machine learning 37,45,46 . The limited availability of highquality and comprehensive meteorological data in India and complexity of the regional topography and climate are also prominent contributing factor for limited number of research.…”
Section: Introductionmentioning
confidence: 99%
“…Many other studies were done by the authors in which rainfall pattern, distribution, frequency, etc. of different North Indian states were studied, that is, Haryana (Chauhan et al., 2022; Nain & Hooda, 2019), Himachal Pradesh (Jaswal et al., 2015), Punjab (Kaur et al., 2021), Rajasthan (Mundetia & Sharma, 2014; Pingale et al., 2013), Uttarakhand (Malik & Kumar, 2020) and Uttar Pradesh (Guhathakurta et al., 2020). Mondal et al.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing trends in precipitation during autumn and winter, whereas decreasing trends during monsoon and spring were reported by Pal and Al-Tabbaa (2011) based on the analysis for the period of 1954-2003. Many other studies were done by the authors in which rainfall pattern, distribution, frequency, etc. of different North Indian states were studied, that is, Haryana (Chauhan et al, 2022;Nain & Hooda, 2019), Himachal Pradesh (Jaswal et al, 2015), Punjab (Kaur et al, 2021), Rajasthan (Mundetia & Sharma, 2014;Pingale et al, 2013), Uttarakhand (Malik & Kumar, 2020) and Uttar Pradesh (Guhathakurta et al, 2020). Mondal et al (2022) showed that the extreme precipitation events across South Asia may increase up to 3.5%-6.6% due to increase in warming from 1.5 to 2.0°C.…”
mentioning
confidence: 99%